ELIMINATION:
You can multiply the second equation by 2:
![\begin{cases}-2x+3y=8\\2x+2y=4\end{cases}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ebc8050lr78k35opmu8dvjyv5qneanxkld.png)
And then add the two equations:
![(-2x+3y)+(2x+2y)=8+4 \iff 5y=12 \iff y=(12)/(5)=2.4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rpgaf6cr4n50vm2in4jgmh1g3h6f7ratc9.png)
And we deduce
![x=2-y = 2-2.4=-0.4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wq52mwmvvj5izcjk32d7b7mgjc21oy003w.png)
SUBSTITUTION:
From the second equation, we derive
![x=2-y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pak2sorh0wou369uuru92h4shajx8moxpx.png)
Plug this expression for x in the first equation:
![-2x+3y=8 \iff -2(2-y)+3y=8 \iff -4+2y+3y=8 \iff 5y=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bzle1utqxcuj83y1he4g0c447sabulu2zy.png)
And from here you proceed in the same way as above.